“MEXANIKA BO‘LIMI” GA DOIR MASALALARNI GRAFIK USULDA MATHCAD DASTURI YORDAMIDA YECHISH METODIKASI - Arabov, J.O. (SCIENCE and SOCIETY, 2022)
The solution of graphic problems to a large extent contributes to a deep mastery of the basics of physics and the formation of physical concepts in students, develops physical thought, and improves the skills of applying knowledge in practice. This article provides some examples and explanations for solving problems in the section of mechanics in a graphical way using software tools.
Keywords: initial speed; speed; acceleration; free fall acceleration; energy; potential energy; kinetic energy; total energy